Implementation of Business Intelligence for Performance Evaluation of a Professional Certification Institution Using Microsoft Power BI - Irsyadulloh Ramadhan Bagus Nuryono; Eman Setiawan; Natalia Damastuti (COREAI: Jurnal Kecerdasan Buatan, Komputasi dan Teknologi Informasi, 2026)
The Cipta Unggul Human Resource Management Professional Certification Body (LSP) faces challenges in its organizational performance evaluation process because operational certification data is still stored in various separate spreadsheet files that have not been optimally integrated. This situation results in manual report preparation, which is time-consuming, prone to data processing errors, and makes it difficult for management to monitor performance achievements quickly and accurately. This study aims to design a Business Intelligence system to evaluate the institution’s performance using Microsoft Power BI. The research method employed is Design Science Research with a qualitative descriptive approach. The research stages included identifying information needs, collecting data for the 2023–2024 operational period, designing a Data Warehouse using the Star Schema model, performing the Extract, Transform, Load (ETL) process, and developing a dashboard based on key performance indicators (KPIs) aligned with the Balanced Scorecard. The research results show that the designed system is capable of integrating previously fragmented data into a single, concise information source, accelerating the reporting process, improving information accuracy, and facilitating interactive monitoring of performance indicators.